P28 Mental health inequalities among men with disability: an intersectional approach. (3rd September 2019) - King, TL; Shields, M; Shakespeare, T; Milner, A; Kavanagh, A
Abstract : Background: Disability is a key social identity or social category that is associated with significant social disadvantage. For men, having a disability can be discordant with their masculine identity. Self-reliance is one component of masculinity that is known to be important to men with disabilities, however it is also known to be associated with adverse mental health outcomes in the broader adult male population. Intersectionality approaches offer a means of examining the way that the effect of self-reliance on mental health might vary between those with and without a disability. Methods: We drew on a sample of 12, 052 men aged 18–55 years from the Ten-to-Men study, a longitudinal cohort study of Australian men and boys. We used survey-weighted adjusted Poisson regression to examine associations between disability and depressive symptoms, adjusting for age, country of birth, indigenous status, education and area disadvantage. We applied an intersectional approach by using effect measure modification (EMM) to examine how conformity to the masculine norm of self-reliance modifies the relationship between disability and depressive symptoms, calculated on both the multiplicative and additive scales. Results: Results showed that men with disabilities who reported higher conformity to self-reliance norms had worse mental health than non-disabled men with low conformity to self-reliance, as measured in terms of depressive symptoms (PRR: 9.40, 95%CI 7.88, 11.22). We found evidence of positive EMM of depressive symptoms by conformity to self-reliance on the additive scale (RERI: 2.84, 95%CI 1.26, 4.42). Conclusion: These results highlight the mental health differences between men with and without disabilities, and provide evidence that high conformity to self-reliance norms exerts a particularly damaging effect on the mental health of men with disabilities. Given that men with disabilities are more likely to rely on help and support from others, these results have important implications for the delivery of services to men with disabilities. The results suggest a role of practitioners and advocates in encouraging men with disabilities to accept support when needed, and also advocate for them to be able to access technologies and other supports that enable them to be more self-reliant.